2019
DOI: 10.36740/wlek201904126
|View full text |Cite
|
Sign up to set email alerts
|

The Parameters of Liver Functional State as a Risk Factor of Edematous Pancreatitis Development Providing of Genetic Determination of Il-4 Production

Abstract: Introduction: One of the main pathophysiological mechanisms of acute pancreatitis development is the damage of pancreas cells and hepatocytes with enzymes activation. Recently, a powerful mechanism of the immune system involvement in the acute pancreatitis pathogenesis, in particular, from the position of genes polymorphism influence attracts more attention. The aim: To study the parameters of liver functional state as risk factors for the development of edematous pancreatitis under the conditions of genetic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
1
1
0
1
Order By: Relevance
“…These mechanisms may explain why GGT affects the occurrence of AP. ALP, ALT, AST, and TBil are serological indicators currently used in clinical practice to reflect liver injury, and studies have shown that indicators of liver damage correlate with the severity of AP disease [23]. However, there is no evidence that the ALP and AST levels are risk factors for AP, which is consistent with the results of our Mendelian analysis.…”
Section: Plos Onesupporting
confidence: 83%
“…These mechanisms may explain why GGT affects the occurrence of AP. ALP, ALT, AST, and TBil are serological indicators currently used in clinical practice to reflect liver injury, and studies have shown that indicators of liver damage correlate with the severity of AP disease [23]. However, there is no evidence that the ALP and AST levels are risk factors for AP, which is consistent with the results of our Mendelian analysis.…”
Section: Plos Onesupporting
confidence: 83%
“…Досі невідомо, яку конкретну роль генетичні чинники відіграють у розвитку цих захворювань [9,10]. Генетичні чинники визначають активність глутатіонового антиоксидантного захисту, взаємопов'язані зі змінами метаболізму жирів та вуглеводів, а також впливають на транспорт та сигнальні шляхи ключових поживних речовин (цинк, селен, йод тощо) для роботи імунної, ендокринної і нервової систем [11,12].…”
Section: вступunclassified
“…About 78% patients with AP present with generalized peritonitis and 26% with severe peritonitis. The overall mortality rate significantly decreased (15-25%) over last decades but remains high [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%